Lubiprostone Increases Spontaneous Bowel Movement Frequency and Quality of Life in Patients With Chronic Idiopathic Constipation - Fukudo, Shin; Hongo, Michio; Kaneko, Hiroshi; Takano, Masahiro; Ueno, Ryuji (Clinical gastroenterology and hepatology, 2015)
Lubiprostone is an activator of the type 2 chloride channel that facilitates spontaneous bowel movement (SBM). We performed phase 3 studies to determine whether lubiprostone increases the frequency of SBM in patients with chronic idiopathic constipation (CIC) in Japan, and whether long-term administration of lubiprostone increases the quality of life of patients with CIC. We performed a randomized, double-blind, placebo-controlled, phase 3 trial of lubiprostone. Patients with CIC (n = 124) were assigned randomly to groups given placebo (n = 62) or lubiprostone (48 μg/day; n = 62) for 4 weeks. The primary efficacy end point was the change from baseline in the weekly average number of SBMs after 1 week of administration. In a long-term study of efficacy and safety, 209 patients with CIC were given lubiprostone (24 μg twice daily) for 48 weeks. Daily administration of lubiprostone induced a significantly greater change, from baseline, in the weekly average number of SBMs at week 1 (increase of 3.7 ± 2.8), compared with placebo (increase of 1.3 ± 1.8; P < .001). The frequency of SBMs during each week of the study period was significantly higher after subjects began receiving lubiprostone than at baseline (P < .0001 at all weeks). Long-term administration of lubiprostone significantly increased scores from the Short-Form health survey and irritable bowel syndrome quality-of-life questionnaire, compared with baseline. We did not observe any severe adverse reactions to lubiprostone. In phase 3 studies in Japan, lubiprostone increased the weekly average number of SBMs and increased the quality of life of patients with CIC. Clinical Trial Notification of the Japanese Regulatory Authorities: 20-3296 and 20-3300.